Delirium related distress experienced by nurses - Inês Pereira Baptista (2022)
Background: Delirium is described as a distressful experience by patients and their families. Among healthcare staff, nurses caring for patients with delirium are the most at risk of high distress related to this syndrome. Aims: To assess nurses' distress related to delirium and the specific symptoms and severity of this syndrome. To identify factors (nurses' sociodemographic and psychological characteristics, professional experience) that may associated to this distress. Methods: A prospective study was carried out with nurses of elderly patients with delirium from the Intensive Care Medicine Department-CHUSJ. Patients with deafness/blindness, inability to communicate or a Glasgow Coma Scale ≤11 were excluded. Delirium was assessed with Confusion Assessment Method. Distress related to delirium, global psychological distress and burnout in nurses were measured with Delirium Experience Questionnaire, Kessler Psychological Distress Scale and Copenhagen Burnout Inventory, respectively. Results: In this study, 26 delirium patients (median age/MA=82y.o) and 18 nurses (MA=32y.o; 89% women) were included. About 46% of the nurses classified the experience of caring for patients in delirium as moderately distressing. Disorientation and psychomotor agitation were the most distressing symptoms. High distress related to delirium was associated with greater personal (rs=0.463;p=0.040) and work-related burnout (rs=0.515;p=0.020), and more global psychological distress (rs=0.583;p=0.007). Conclusion: Caring for patients with delirium is distressing for nurses, particularly if disorientation and psychomotor agitation are present and if nurses presented high burnout or psychological distress. This study highlights the importance of more specific delirium training for nurses and the need for the developing support and coping strategies for all professionals dealing with these patients.